Deskripsi Agronomi Berbagai Varietas Ketan Pada Dataran Medium Agronomic Description Of Various Varieties Of Glutinous Rice In Medium Plains - chairunnisa vanidarisma (AGRONISMA, 2021)
The agronomic character is closely related to the main objective of increasing glutinous rice production with yield and yield components. Therefore, it is necessary to identify and describe the agronomic of 16 kinds of glutinous rice varieties. This study aims to obtain descriptive data on the agronomic characters of 16 varieties of glutinous rice in rice fields in the medium plains. The design used was a factorial randomized design (RAK). The treatments were 16 kinds of glutinous rice varieties, repeated 3 times so that the total experimental units were 54 units. Each experimental unit contained 16 clumps and four plants were taken as samples of 16 varieties of treatment plants. The results showed that the 16 varieties of glutinous rice had an effect on plant growth and yield. The observed growth parameters were the number of leaves and leaf area, while the yield parameters observed were the number of panicles and dry grain weight per hectare. For good growth, namely in V2 (Lusi Jember variety) and low growth in V12 (PYM.20 West female variety). Meanwhile, the harvest parameters were good in V1 and V2 (lokbon 1 black variety and lusi jember variety) and low yields at V11 (wuluh Hitam parang bhanyakan variety).